Effects of different protein sources on growth performance of nursery pigs - K R Lawrence; C W Hastad; S M Hanni; M R Barker; B W James; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A total of 170 weanling pigs (initially 16.4 lb) were used to evaluate the effects of alternative protein sources on growth performance of pigs fed from d 5 to 26 after weaning. All pigs were fed a common diet from weaning to d 5. The five dietary treatments were cornsoybean meal-based and included a control diet containing 10% dried whey, or the control diet with 5% select menhaden fish meal, 2.5% spray-dried blood cells, 3.73% enzymatically hydrolyzed wheat gluten (Source 1), or 3.51% flash-dried wheat gluten (Source 2). No differences were observed in overall ADG and ADFI; however, pigs fed the diets containing 2.5% blood cells or 5% select menhaden fish meal numerically had the best overall ADG compared to pigs fed the control diet, with pigs fed either wheat gluten sources having intermediate growth. Feed efficiency was improved for pigs fed 5% select menhaden fish meal compared with those fed the control diet, and pigs fed the other diets were intermediate. There were no differences (P<0.05) in ADG, ADFI, or F/G between wheat gluten sources.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Protein sources; Wheat gluten; Weanling pigs; Swine